The Open Access Observatory - Rovira, Anna; Labastida, Ignasi (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
Open Access seems to have reached a flipping point and become a real option when researchers decide where to publish. However the figures provided when someone gives percentages are not clear because there is a lack of coincidence when defining open access. In this paper we would like to explain the project initiated by two Catalan universities, the Universitat de Barcelona (UB) and the Universitat Politècnica de Catalunya (UPC), which decided to use a common methodology to measure the different levels of open access in their institution. A methodology that can be used by any institution around the world to make visible their evolution and trends in the Open Access movement. Moreover, we also share a methodology to estimate the expenditure on fees to publish open access. In these two research institutions there is not a central system for processing those payments and therefore we need to make estimations in order to know how much we pay each year. Again, we think this methodology can be used worldwide. Both initiatives configure the initial work of what we called the Open Access Observatory, a project that was created aimed at providing and sharing evidences, methodologies and data in relation to open access publications.